(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The nucleus of excavation is based on the results which involve exponential function. The results of Exton and Pathan Yasmeen are used with a view to obtain multivariable generating functions which are partly bilateral and partly unilateral.